Market-based IPO Reforms, Investor Sentiment and information asymmetry: Evidence from the Chinese IPO underpricing - QIN, YIFEI (2020)
IPO underpricing is a world-wide discussed topic, particularly in China IPO market. Learning from corresponding regulation, the existing theories and empirical researches, my dissertation analyzed 1306 listing samples from SSE and SZSE, which covered the time of 2011 to 2018. I proposed that western experience could explain to the Chinese IPO market in some certain degree because of distinct characteristics and I majorly interpreted IPO underpricing phenomenon in China A-share market through three main sides, including information asymmetry, overconfident and speculative investors’ behaviour and specific IPO regulation lead to an imbalance of demand and supply. To develop a healthier and efficient IPO market, new share issuance system was successively updated. The previous three IPO reform effectively diminished the problem of the high level of IPO underpricing, from 114.87% in 2008 to 27.69% in 2013. The level of IPO underpricing was extremely high after undergoing the 4th new share reform, the explanations were given. First, the IPO market was reopened and created a bull market. Second, the implementation of rising or drop limit in new shares’ price increased the positive individual’s investment sentiment, since most of the new shares’ price kept touching the limit and continued to go up in the following transaction days. Deal with this problem is a long journey for China, the further revised reforms are still required to adapt the newest development of the world and state of the Chinese IPO market.